Autorzy:Adam Makowski, Tomasz Masłowski, Anna Toruńska
Wydawnictwo:WSiP
Rok wydania:2015
Doprowadź wyrażenie do najprostszej postaci 4.57 gwiazdek na podstawie 14 opinii

Doprowadź wyrażenie do najprostszej postaci

15Zadanie
16Zadanie
17Zadanie
18Zadanie
19Zadanie
20Zadanie
21Zadanie

`a)\ 2x(3x+5)-3(x^2-3x+2)=` 

`\ \ \ =ul(6x^2)+ul(ul(10x))-ul(3x^2)+ul(ul(9x))-6=` 

`\ \ \ =3x^2+19x-6` 

 

`b)\ -3(2x^2+x-7)-2x(x-3)=` 

`\ \ \ =ul(-6x^2)-ul(ul(3x))+21-ul(2x^2)+ul(ul(6x))=` 

`\ \ \ =-8x^2+3x+21` 

 

`c)\ 3/4(2 2/3x-12)+2/3x(6x-4 1/2)=` 

`\ \ \ =3/4(8/3x-12)+2/3x(6x-9/2)=` 

`\ \ \ =strike3^1/strike4^1*strike8^2/strike3^1x-3/strike4^1*strike12^3+2/strike3^1x*strike6^2x-strike2^1/strike3^1x*strike9^3/strike2^1=` 

`\ \ \ =2x-9+4x^2-3x=4x^2-x-9` 

 

`d)\ 1/3(1 1/2x-2 1/4)-1/2(3x-1/2)=` 

`\ \ \ =1/3(3/2x-9/4)-1/2(3x-1/2)=` 

`\ \ \ =1/2x-3/4-3/2x+1/4=` 

`\ \ \ =-2/2x-2/4=-x-1/2`